CLINICAL-PATHOGENIC IMPORTANCE OF CORRELATION BETWEEN HISTOCHEMICAL INDICES OF BLOOD SYSTEM AND RHEUMATOID FACTOR IN PATIENTS WITH RHEUMATOID ARTHRITIS - A B Zborovsky; B V Zavodovsky; A V Rvacliev; O V Bykova; T V Serdiukova; Pankratova TA (Научно-практическая ревматология, 2001)
Summary Relation between rheumatoid factor (RF) and levels of Myeloperoxidase (MPO), Na*-K +-A TPh- ase (ATPh-ase), 5'-Nucleotidase (5 ’-NT), Succinate dehydrogenase (SDG) in cells of peripheral blood of rheumatoid arthritis (RA) patients was investigated. 83 RA patients were observed. The activities of MPO, ATP-ase, 5’NT, SDG in blood cells were determined by hystochemical methods. In patients having increasing MPO activity in monocytes, normal level of SDG in lymphocytes and decreasing of 5'NT in monocytes and lymphocytes increasing of RF level was noted in 3 weeks after hystochemical changes (p<0.05). Determination of MPO in monocytes was the most informative test for forecasting of immunological changes in RA. The role of macrophage system in RA is discussed.